2019
DOI: 10.1002/pon.5106
|View full text |Cite
|
Sign up to set email alerts
|

Dispositional mindfulness, self‐compassion, and compassion from others as moderators between stress and depression in caregivers of patients with lung cancer

Abstract: Objective The present study aimed to identify the most important protective factors predicting caregivers' depressive symptoms among factors of caregivers' dispositional mindfulness, self‐compassion, compassion from others, and patients' dispositional mindfulness and their moderator effects on the relationship between caregiving stress and depressive symptoms. Methods A total of 72 lung cancer outpatients and their family caregivers participated in this study. Family caregivers completed the Kingston Caregiver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 38 publications
4
28
0
Order By: Relevance
“…Participants learned and practiced relaxation, cognitive restructuring, and assertive communication as well as the ability to choose an effective coping technique accounting for the controllability of the stressor (problem-focused coping vs emotion-focused coping). 19 Although studies show that proficiency with skills, such as engaging in mindful awareness and self-compassion, may be linked to better management of distress among caregivers in other cancer populations, 20 evidence of the impact of psychosocial interventions on coping efforts in the HCT caregiving setting is lacking and mixed. 21,22 To our knowledge, ours is the first to demonstrate improved coping in caregivers in the HCT setting.…”
Section: Discussionmentioning
confidence: 99%
“…Participants learned and practiced relaxation, cognitive restructuring, and assertive communication as well as the ability to choose an effective coping technique accounting for the controllability of the stressor (problem-focused coping vs emotion-focused coping). 19 Although studies show that proficiency with skills, such as engaging in mindful awareness and self-compassion, may be linked to better management of distress among caregivers in other cancer populations, 20 evidence of the impact of psychosocial interventions on coping efforts in the HCT caregiving setting is lacking and mixed. 21,22 To our knowledge, ours is the first to demonstrate improved coping in caregivers in the HCT setting.…”
Section: Discussionmentioning
confidence: 99%
“…Although still relatively recent in terms of development, the CEAS are beginning to be used within compassion-focused research. In general population samples from Australia and Singapore (Steindl et al, 2018;Steindl et al, 2019), and in caregivers of people with lung cancer in Taiwan (Hsieh et al, 2019), the CEAS have performed acceptably, with good levels of internal reliability reported (Cronbach's α from .79 to .95). In contrast, a recent study conducted with female survivors of intimate partner violence in Colombia reported excluding the CEAS as a planned outcome measure, as participants did not understand multiple items during piloting (Naismith et al, 2020).…”
Section: Introductionmentioning
confidence: 90%
“…Tate et al [ 25 ] showed that mindfulness created a new and alternative perspective on how patients can change their perceptions of themselves and the world around them. Hsieh et al [ 26 ] showed that mindfulness was significantly associated with stress and depressive symptoms in the caregivers of the lung cancer patients. Zhong et al [ 27 ] also indicated that mindfulness was negatively associated with perceived stress, anxiety and depression, and loss of self-confidence in Chinese patients with gastrointestinal cancer.…”
Section: Introductionmentioning
confidence: 99%